Pendampingan Penyusunan Laporan Keuangan untuk Pemilik UMKM Sesuai dengan SAK EMKM dan Perhitungan Pajak - Puji Astuti Rahayu; Sylvia Fettry Elvira; Felisia Liu; Monica Paramita Ratna (University of Merdeka Malang, 2021)
Nowadays, the conditions of economics require housewives to be more creative in finding additional income to support their families. One alternative is to establish SMEs. SME owners need to make regular financial reports and fulfill their tax obligations. To help them, this activity was held at the Gereja Paroki Kamuning Bandung, with participants from the Wanita Katolik Republik Indonesia (WKRI) Paroki Kamuning Bandung. Many of the participants have not made financial reports or fulfilled their obligations as taxpayers. They do not have sufficient information and knowledge about it. The objective of this activity is to provide better understanding and assistance in preparing financial reports and calculating the tax payable based on Government Regulation or PP No. 23 of 2018. These activities consist of first, understanding the condition of the business and understanding of financial statements and tax obligations. Second, we compile a guidebook that consists of steps in making financial reports and calculating payable taxes, conducting training and assistance in preparing financial reports and calculating taxes. The result of this activity is an increase in the participants' understanding of the preparation of financial reports, how to calculate taxes owed, and the reasons why MSME owners must carry out their tax obligations.DOI: https://doi.org/10.26905/abdimas.v6i2.5169